The Law of Minimum Sentences: Judicial Responses and Responsibility - Paciocco, David M. (Canadian Criminal Law Review, 2015)
Judges are obliged to follow the law, including by imposing mandatory minimum sentences. This can create a moral dilemma. Judges who justify punishment based on its utility in reducing crime may believe that minimum sentences are pointlessly harsh because they do not enhance public protection. Judges who justify punishment based on retributivist theory may feel that mandatory minimum sentences are excessive and therefore unjust. This paper contends that in their effort to impose just and useful sentences, judges tend to seek out and use available legal tools to reduce perceived unfairness. Statutory interpretation, the use of the principle of totality in multiple count prosecutions, and the selective deployment of sentencing tools have all been used to this end. The author contends that striving to constrain the impact of minimum sentences in this way does not corrupt the administration of justice. Instead it is a legitimate, predictable and inevitable outcome.
Num Pages: 57 Place: Toronto, Canada